Microstructures: Mechanisms and Microenvironment Investigation of Cellularized High Density Gradient Collagen Matrices via Densification (Adv. Funct. Mater. 16/2016). (April 2016) - Novak, Tyler; Seelbinder, Benjamin; Twitchell, Celina M.; van Donkelaar, Corrinus C.; Voytik‐Harbin, Sherry L.; Neu, Corey P.
Abstract : Biomaterials often have characteristic spatial gradients in physical properties that lead to specialized function. On page 2617, C. P. Neu and co‐workers form gradient matrices of natural biopolymers using a densification process that exudes fluid from the structure, leading to a reproducible reorganization of collagen and embedded cells. High‐density regions show increased fibril packing, mechanical properties, and fibril thickness, on par with values observed in native tissues like articular cartilage.